2022
DOI: 10.1111/1749-4877.12692
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the morphological patterns of a subantarctic eelpout: a geometric morphometric approach

Abstract: Phenotypic variation in organisms depends on the genotype and the environmental constraints of the habitat that they exploit. Therefore, for marine species inhabiting contrasting aquatic conditions, it is expected to find covariation between the shape and its spatial distribution. We studied the morphology of the head and cephalic sensory canals of the eelpout Austrolycus depressiceps (4.5–22.5 cm TL) across its latitudinal distribution in South Pacific (45°S–55°S). Geometric morphometric analyses show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Covariation between head shape, particularly eye size and location, and length (SL), has been previously detected in several fish species (e.g., zoarcids, Orrego et al, 2023) and represents a noticeable allometric effect found in juvenile fish. Although the evolutionary allometry was low, the static allometry of each species was relatively high.…”
Section: Discussionmentioning
confidence: 96%
“…Covariation between head shape, particularly eye size and location, and length (SL), has been previously detected in several fish species (e.g., zoarcids, Orrego et al, 2023) and represents a noticeable allometric effect found in juvenile fish. Although the evolutionary allometry was low, the static allometry of each species was relatively high.…”
Section: Discussionmentioning
confidence: 96%